Deir el-Bahari. Temple of Tuthmosis III, campaigns 2012–2013 - Monika Dolińska (Polish Archaeology in the Mediterranean, 2015)
In 2012 and 2013 the mission continued research and documentation work, concentratingon scenes located in the Hypostyle Hall, the Bark Room, and rooms D, G and H. Dozensof painted stone fragments were cleaned and protected. Photoscanning techniques were used toimprove detailed rendering of the temple. New photomontages were produced and subsequentwalls were drawn, joining previously separate scenes.